The Balance of Legal Liability in Marine Cargo Insurance Based on the Principle of Subrogation in Indonesia - Anggun Nurfani nurfani; Sunaryo; Hamzah; Kasmawati (NEGREI: Academic Journal of Law and Governance, 2025)
This article examines the implementation of subrogation rights in marine cargo insurance contracts in Indonesia, with an emphasis on the balance of legal responsibilities in subrogation practices. Subrogation rights, which allow the insurer to assume the legal position of the insured after claim payment, often face issues of unequal legal protection, particularly in cases involving third parties. This study employs a normative juridical method, using a statutory approach and case study analysis of court decisions. Findings indicate a lack of clear regulations and mechanisms ensuring a balance in legal responsibilities related to subrogation rights. Therefore, a reconstruction of contractual norms and regulatory frameworks is needed to guarantee proportional legal protection for all parties involved. The state holds a crucial role that must be optimized through the formulation of legal norms and regulations to ensure subrogation rights are exercised proportionally